Team Incentives, Task Assignment, and Performance: A Field Experiment - Josse Delfgaauw; Robert Dur; Michiel Souverijn (Institute of Labor Economics (IZA), 2017)
The performance of a work team commonly depends on the effort exerted by the team members as well as on the division of tasks among them. However, when leaders assign tasks to team members, performance is usually not the only consideration. Favouritism, employees' seniority, employees' preferences over tasks, and fairness considerations often play a role as well. Team incentives have the potential to curtail the role of these factors in favor of performance – in particular when the incentive plan includes both the leader and the team members. This paper presents the results of a field experiment designed to study the effects of such team incentives on task assignment and performance. We introduce team incentives in a random subsets of 108 stores of a Dutch retail chain. We find no effect of the incentive, neither on task assignment nor on performance.
Keywords: C93; M12; M52; 330; team incentives; task assignment; field experiment